Meningkatkan nilai tambah perekonomian lokal melalui pengembangan agrowisata dan inovasi produk jambu di Ngargoyoso Karanganyar - Heni Susilowati; Titin Hargyatni; Ratnaningrum Ratnaningrum; Pemilia Sulistyowati; Jaelani Jaelani; Asnawi Hidayat; Kusna Djati Purnama (Nur Science Institute, 2026)
This Community Service Program (PkM) aims to increase the value added of Puja red guava and strengthen farmers’ independence in Ngargoyoso, Karanganyar Regency, through the development of agrotourism, innovation in processed products, and the implementation of marketing strategies. However, red guava production has the potential to support local economic growth, but marketing remains dominated by fresh fruit sales and dependence on middlemen, resulting in low economic returns for farmers. This program applied a participatory approach consisting of Participatory Rural Appraisal (PRA), Participatory Action Research (PAR), and Community-Based Research (CBR). SWOT analysis was used to assess the sustainability of Puja Red Guava Agrotourism. The PkM program findings indicate that strengths in raw materials availability and product uniqueness, while weaknesses include managerial capacity and limited market access. External threats include price fluctuations and the conversion of land into restaurants. However, the development arises from advances in digital technology, the use of social media, wider marketing reach, and government support for MSME development. Overall, this program demonstrates strong potential for business diversification, increased bargaining power, and sustainable agrotourism development in Ngargoyoso.